Strategi Pengembangan Kewirausahaan Untuk Meningkatkan Minat Dan Motivasi Siswa Kelas XI SMAN 6 Bengkulu Selatan - Putri, Pongki Resmala; Soleh, Ahmad; Putra, Iswidana Utama; Harwini, Dewi; Fitriano, Yun (Jurnal Dehasen Untuk Negeri, 2024)
Entrepreneurship is a creative and innovative ability that is used as a basis, tips and resources for seeking opportunities for success. The essence of entrepreneurship is the ability to create something new and different (create new and different) through creative and innovative thinking to create opportunities. As time goes by, an entrepreneurial spirit is needed that grows from the younger generation to support the national economy through entrepreneurship. This Community Service activity aims to provide class XI students at SMAN 6 South Bengkulu with an introduction to learning about entrepreneurship, interests and motivation as well as the benefits of entrepreneurship. This activity explains the concept of starting a business, including a business plan, various business opportunities, the benefits of starting a business, and the characteristics of entrepreneurship. There is a need for motivation in the field of entrepreneurship for students so that they can increase class XI students' interest in entrepreneurship which can later help the economy for themselves and their families. It is hoped that class.